Improving interprofessional handover on labor and delivery: A needs assessment study. - Leung, Wynne I.; Emery, Crystal; Egan, Rylan (Journal of Interprofessional Care)
Handover is the transfer of important clinical information between health providers. The current report describes a needs assessment of interprofessional labor and delivery handover at an urban hospital in Canada. The goal of this study was to explore the perceptions of the current handover meeting and opportunities for improvement. Using a constructivist paradigm, we conducted 28 semi-structured inter- views with handover participants. We used a recruitment grid to ensure we included the voices of participants representing each profession involved in interprofessional handover meetings. An inductive process was used to code the interview transcripts and theme the data. Major themes identified were: (1) Interprofessional handover contributes positively to team situational awareness, interprofessional relationships, and team communication; (2) Handover could be better if it had a more defined process; (3) Interprofessional handover can lead to feelings of intimidation; and (4) Interprofessional handovers on the labor and delivery unit in our setting need increased inclusivity of midwives. From these themes, continued development of interprofessional handover meetings on labor and delivery should be aimed at a formal definition of the scope and process for these meetings reducing feelings of intimidation, increased integration of Midwifery providers, and continued improvement of relationships between different professions and practitioners on labor and delivery.